Increasing the level of certainty in medical diagnosis. Using AHP/ANP with compatibility index G in support of medical diagnosis. (2016) - Garuti, Claudio; Sandoval, Mario
This paper is based on the development of a web-based tool, in support of medical decision making called medical sapiens (MS), oriented to improve diagnostic accuracy and diminishing the uncertainty of the initial diagnosis. It has been developed for four years working with several senior physicians from Medicine Faculty of Los Andes University, and is currently being installed in a public hospital and in a private sport centre in Santiago in its testing mode. The results of this work show that medical certainty grows up significantly when applying this new approach for the diagnosis issue, mainly due to its better way of coping to intrinsic complexity.